2012
DOI: 10.1007/s11104-012-1460-8
|View full text |Cite
|
Sign up to set email alerts
|

Tissue density determines the water storage characteristics of crop residues

Abstract: Background and aims The water storage properties of plant residues play an important role in the regulation of water retention and water transport in no-till agricultural soils. The objective of this work was to understand how the characteristics of crop residues determine their water absorption and retention properties. Methods A range of eleven undecomposed crop residues and maize stem residue of different particle sizes at three stages of decomposition were characterized regarding their physical and chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 37 publications
4
34
1
1
Order By: Relevance
“…While these contrasting results do not undermine the applicability of substrate initial N concentrations and C/N ratio as plant litter quality indicators, they imply the necessity for prudent decision making in selecting plant residues for soil fertility improvement based on multiple plant and soil factors. It is therefore reasonable to assume that unlike the initial N concentrations of the plant residues and their C/N ratios, their decomposition and N mineralization may be related to: (1) different decomposer communities that may have developed on the plant residues based on their intrinsic qualities (Cobo et al 2002); (2) other plant quality variables such as lignin, polyphenol, hemicellulose concentrations and their ratios with N; (3) C/N ratio of soil; as well as (4) the water retention capacity of plant residues which although unassessed in this study have been shown to influence plant residue decomposition and N mineralization (Palm et al 2001;Iqbal et al 2013;Makkonen et al 2013). Based on the results on N mineralization, leaf biomass application of T. diversifolia, G. sepium, L. leucocephala and S. spectabilis are expected to improve soil N availability and subsequent uptake by crops for increased biological yield.…”
Section: Discussionmentioning
confidence: 90%
“…While these contrasting results do not undermine the applicability of substrate initial N concentrations and C/N ratio as plant litter quality indicators, they imply the necessity for prudent decision making in selecting plant residues for soil fertility improvement based on multiple plant and soil factors. It is therefore reasonable to assume that unlike the initial N concentrations of the plant residues and their C/N ratios, their decomposition and N mineralization may be related to: (1) different decomposer communities that may have developed on the plant residues based on their intrinsic qualities (Cobo et al 2002); (2) other plant quality variables such as lignin, polyphenol, hemicellulose concentrations and their ratios with N; (3) C/N ratio of soil; as well as (4) the water retention capacity of plant residues which although unassessed in this study have been shown to influence plant residue decomposition and N mineralization (Palm et al 2001;Iqbal et al 2013;Makkonen et al 2013). Based on the results on N mineralization, leaf biomass application of T. diversifolia, G. sepium, L. leucocephala and S. spectabilis are expected to improve soil N availability and subsequent uptake by crops for increased biological yield.…”
Section: Discussionmentioning
confidence: 90%
“…Pourtant, nous avons travaillé avec des quantités variables de résidus de plantes, ayant des caractéristiques différentes, et sur des exploitations et situations climatiques différentes au moment des récoltes et au cours des cinétiques de décomposition. Iqbal et al (2013) ont montré sur les tiges de ces mêmes espèces une différence importante de la composition chimique (par exemple, le rapport fraction soluble : fraction lignine égale à 1,24 pour le blé et 3,92 pour le maïs) et des propriétés physiques (par exemple, la densité des tiges de 0,35 g cm À3 pour le blé et 0,10 g cm À3 pour le maïs). Or, ces cinétiques se superposent selon un ajustement proportionnel à la biomasse initialement présente, selon des jours « normalisés » sur le seul critère de la température de l'air.…”
Section: Discussionunclassified
“…Under dry conditions, when land was fallow after harvesting, the topographic factor became important in determining soil moisture content. However, a residual cover crop remained after harvesting, and any type of conservation tillage may also affect soil moisture [68][69][70][71].…”
Section: Correlations Between Soil Moisture and Environmental Variablesmentioning
confidence: 99%